Duplicate references in the 'Introduction' and 'Discussion' sections of scientific articles on physical education and sports - Leonid Podrigalo; Sergii Iermakov (Pedagogy of Health)
Background and Study Aim. In the context of the increasing volume of scientific publications, the adequacy and effectiveness of source use in key sections of articles become crucial tasks. This requires detailed consideration, especially in light of potential duplication of references, which can affect the perception of originality and depth of research. The purpose of this article is to investigate the nature and impact of duplicate references in the 'Introduction' and 'Discussion' sections of scientific articles on physical education and sports.